PEYAMİ SAFA`NIN YALNIZIZ ROMANINDA SÖZ DİZİMİ - GÜZEL, FERDİ (Fırat Üniveristesi, 2007)
In this work, 40 pages that are chose from one of the most important author of ourliterature, Peyami Safa?s novel named ?Yalnız?, are examined in point of syntax. Our aim is to contribute to syntax works and to determine how Peyami Safa uses the languageand to reach some informations about his style by using this work.We got these results from the examination we did:1. We determined 952 sentences from 40 pages that we chose from different partsof the work. We examined the sentences that we determined, according to theirstructures. 633 of these sentences are simple clauses, 17 of these are conditional clauses,31 of these are independent clauses, 96 of these are coordinete sentences, 85 of these aredependent clauses, 89 of these are uncompleted clauses. The most used sentence issimple sentence with % 66.49. The proportion of others are like this: coordinetesentences % 10.08, uncompleted clauses % 9.35, dependent clauses % 8.93, independentclauses % 3.26, conditional clauses % 1.79.2. We examined simple and complex sentences according to predicate?s place,predicate?s type and predicate?s meaning. The proportion of these sentences, 681 in total,are like this:Sentences according to predicate?s place: rugular sentences % 88.11, invertedsentences % 11.89Sentences according to predicate?s type: noun clauses % 26.87, verbal clauses %73.13Sentences according to predicate?s meaning: positive sentences %74.89, negativesentences % 15.27, guestion sentences % 9.843. We determined 3077 word groups in 40 pages that we examined. Adjectivephrases form more than one third of the word proups. The proportion adjective phrasesare % 36.20. The proportion of noun phrases are % 22.32, verbal compounds are %10.33,preposition groups are % 8.64.4. İ is seen that the author used short sentences mostly. According the wordtnumber examination on simple and complex sentences, %12.19 of sentences are formedof two words, % 14.80 of them are formed of three words, % 14.54 of them are formed offour words, % 11.16 of them are formed of five words, % 9.10 of them are formed of sixwords.As the gotten datums are interpreted, it is reached that Peyami Safa is very skilledat making sentences and using language according to contents and gives importance todescription.Key Words: Peyami Safa, Yalnız, sentence, word group , description
The syntax in the novel Yalnızız of Peyami Safa
Keywords: Türk Dili ve Edebiyatı